The disaster preparedness of nanotechnology at Research Center in Northern Region: A case study - Roslan, Firzana; Zulhumadi, Faisal (Universiti Utara Malaysia, 2020)
This study aims to identify the preparedness of a research center in the Northern Region towards disaster. A research Centre of nanotechnology contributes to the technology and education sectors. However, it is hard for them to keep their business because nanotech which is still new in industry because of not much exposure in the technology industry. Thus, this study focused on identifying the factors of effective disaster and emergency planning, and the possible solution of the research center in the Northern Region. This study design used qualitative research methods. The respondent is a senior worker from the Institute of Nano Electronic Engineering (INEE) that belongs to Universiti Malaysia Perlis which is located at Perlis. The result showed that there are many factors that effective for disaster preparedness which is emergency response among workers, security management, and interoperability that is incompatible communication equipment. The results of this study provide a solution to the research center for the disaster preparedness which is hired the skilled worker and gives incentives to the excellent workers, implement the right system to replace the data storage system, and keep improving the communication equipment for emergency response. As implications, this study has resulted in the research center to aware of disaster preparedness in order to help them compete and sustain their businesses in the industry that help them sustain in the nanotech industry.